Output voltage stabilization of non-ideal DC-DC Zeta converter with output voltage error elimination via hybrid control - Sarkawi, Hafez; Mispan, Mohd Syafiq; Idris, Muhammad Idzdihar; Mohd Ridzuan, Noridah (Scientific Research Publishing, 2025)
In this paper, we proposed an output voltage stabilization of a DC-DC Zeta converter using hybrid control. We modeled the Zeta converter under continuous conduction mode operation. We derived a switching control law that brings the output voltage to the desired level. Due to infinite switching occurring at the desired level, we enhanced the switching control law by allowing a sizeable output voltage ripple. We derived mathematical models that allow one to choose the desired switching frequency. In practice, the existence of the non-ideal properties of the Zeta converter results in steady-state output voltage error. By analyzing the power loss in the zeta converter, we proposed an improved switching control law that eliminates the steady-state output voltage error. The effectiveness of the proposed method is illustrated with simulation results.